Staying or moving: government compliance in post-Zomian Laos - Sprenger, Guido (Rural life in late socialism, 2023)
Abstract James C. Scott claimed that upland Southeast Asians consider their good life as dependent on their autonomy from the state. Given that the state today is present in various forms in the uplands, current uplanders can be considered as post-Zomian. Staying and moving represent two contrastive values in this region whose realisation serves to make a good life possible. This chapter considers these values through the issue of resettlement in Laos, a situation in which local values intersect with or contradict government planning. Even in situations in which the state demonstrates its hegemony and force, ethnic Rmeet uplanders tend to stress their own agency. Therefore, resettlement and its avoidance may both appear as the realisation of local values, sometimes in the shape of ‘village agency’, as the good life is seen as life in a community.
Gesehen am 20.03.2024